Quantitative cervical spine injury responses in whiplash loading with a numerical method of natural neural reflex consideration. (June 2022) - Liang, Ziyang; MO, Fuhao; Zheng, Zhefen; Li, Yuandong; Tian, Ye; Jiang, Xiaobing; Liu, Tang
Highlights: We established and validated an active FE head-neck model at multi-levels, and demonstrated an important role of natural neural reflex control in limiting head-neck rotation and injury responses. The results show that integrating neural reflex effects should be necessary to accurately predict head-neck biomechanical responses when using a numerical method. In a typical spinal injury loading condition (whiplash), tissue load concentration locations as well as stress/strain levels of the head-neck system were both changed due to neural reflex control, which were evidently transferred to a lower cervical spine region to reduce injury severity. Abstract: Background and objective: Neural reflex is hypothesized as a regulating step in spine stabilizing system. However, neural reflex control is still in its infancy to consider in the previous finite element analysis of head-neck system for various applications. The purpose of this study is to investigate the influences of neural reflex control on neck biomechanical responses, then provide a new way to achieve an accurate biomechanical analysis for head-neck system with a finite element model. Methods: A new FE head-neck model with detailed active muscles and spinal cord modeling was established and globally validated at multi-levels. Then, it was coupled with our previously developed neuromuscular head-neck model to analyze the effects of vestibular and proprioceptive reflexes on biomechanical responses of head-neck system in a typical spinal injury loading condition (whiplash). The obtained effects were further analyzed by comparing a review of epidemiologic data on cervical spine injury situations. Result: The results showed that the active model (AM) with neural reflex control obviously presented both rational head-neck kinematics and tissue injury risk referring to the previous experimental and epidemiologic studies, when compared with the passive model (PM) without it. Tissue load concentration locations as well as stress/strain levels were both changed due to the muscle activation forces caused by neural reflex control during the whole loading process. For the bony structures, the AM showed a peak stress level accounting for only about 25% of the PM. For the discs, the stress concentrated location was transferred from C2-C6 in the PM to C4-C6 in the AM. For the spinal cord, the strain concentrated locations were transferred from C1 segment to around C4 segment when the effects of neural reflex control were implemented, while the gray matter and white matter peak strains were reduced to 1/3 and 1/2 of the PM, respectively. All these were well correlated with epidemiological studies on clinical cervical spine injuries. Conclusion: In summary, the present work demonstrated necessity of considering neural reflex in FE analysis of a head-neck system as well as our model biofidelity. Overall results also verified the previous hypothesis and further quantitatively indicated that the muscle activation caused by neural reflex is providing a protection for the neck in impact loading by decreasing the strain level and changing the possible injury to lower spinal cord level to reduce injury severity.